A Universidade de Coimbra e a Reforma Pombalina de 1772 - Nunes, Cristiane Tavares Fonseca de Moraes (2013)
This dissertation had as its objective to investigate the impact of the Pombaline Reforms on the University of Coimbra, in 1772. In this sense, it was used several works on political, economic, cultural and educational history which referred to that period as well as some theoretical texts concerning the concept of nation. Moreover, as the main source of this research, among other documents, it was consulted Pombaline legislation, the classical historiography on the subject, especially CompêndioHistórico (1771) and Novos Estatutos (1772) taking into consideration that they were the underlying components of the new University of Coimbra by its mentor, Sebastião José de Carvalho e Melo, Marquis of Pombal. In order to conclude, it was evidenced that the educational reform was attached to a pedagogical syllabus, whose purpose was not only the modernization of Portugal but also opposed to every system influenced by Jesuits, which was previously predominant in Portugal.